Nα-acetyl-L-ornithine deacetylase from Escherichia coli and a ninhydrin-based assay to enable inhibitor identification - Kelley, Emma H.; Osipiuk, Jerzy; Korbas, Malgorzata; Endres, Michael; Bland, Alayna; Ehrman, Victoria; Joachimiak, Andrzej; Olsen, Kenneth W.; Becker, Daniel P. (Frontiers in Chemistry, 2024)
Bacteria are becoming increasingly resistant to antibiotics, therefore there is an urgent need for new classes of antibiotics to fight antibiotic resistance. Mammals do not express N ɑacetyl-L-ornithine deacetylase (ArgE), an enzyme that is critical for bacterial survival and growth, thus ArgE provides a promising new antibiotic drug target, as inhibitors would not suffer from mechanism-based toxicity. A new ninhydrin-based assay was designed and validated, including the synthesis of substrate analog N 5 ,N 5 -di-methyl N  -acetyl-L-ornithine substrate (kcat/Km = 7.32 ± 0.94 x 10 4 M -1 s -1 ). This new assay enables screening of potential inhibitors that absorb in the UV region, and thus is superior to the historic 214 nm assay. Using this new ninhydrin-based assay, captopril was confirmed as an ArgE inhibitor (IC50 = 58.7 μM; Ki = 37.1 ± 0.85 μM), and a number of phenylboronic acid derivatives were identified as inhibitors, including 4-diethylaminophenylboronic acid (IC50 = 50.1 μM). Selected inhibitors were also tested in a thermal shift assay with ArgE using SYPRO Orange dye against Escherichia coli ArgE to observe the stability of the enzyme in the presence of inhibitors (captopril Ki = 35.9 ± 5.1 μM). The active site structure of di-Zn EcArgE was confirmed using X-ray absorption spectroscopy, and we report two X-ray crystal structures of E. coli ArgE. In summary, we describe the development of a new ninhydrin-based assay for ArgE, identification of captopril and phenylboronic acids as ArgE inhibitors, thermal shift studies with ArgE + captopril, and the first two crystal structures published of ArgE (mono-Zn and di-Zn).